Self‐managing illicit stimulant use: A qualitative study with patients receiving injectable opioid agonist treatment. (25th June 2020) - Palis, Heather; Harrison, Scott; MacDonald, Scott; Marsh, David C.; Schechter, Martin T.; Oviedo‐Joekes, Eugenia
Abstract: Introduction and Aims: Illicit stimulant use is prevalent among patients receiving injectable opioid agonist treatment (iOAT) and has been associated with early treatment discontinuation and illicit opioid use. Despite these concerns, little is known about the use of illicit stimulants in this population. As such, this study aimed to explore the processes by which patients receiving iOAT engage in the use of illicit stimulants. Design and Methods: One‐on‐one in‐depth qualitative interviews were conducted. Data collection and analysis followed an iterative approach of coding, searching for meaning, and returning to data collection to saturate categories and explicate relationships between them. Participants were patients receiving iOAT in Vancouver, Canada that reported the use of illicit stimulants ( n = 31). Results: The process of 'self‐managing illicit stimulant use' was constructed from the data. This process was made up of three interrelated categories reflecting participants' engagement in illicit stimulant use: (i) distancing from the street environment; (ii) taking control of use; and (iii) mobilising support (clinical and social). Discussion and Conclusions: For patients with opioid use disorder and concurrent stimulant use disorder, access to iOAT can promote the self‐management of illicit stimulant use. Daily visits to the clinic for opioid agonist treatment present an important opportunity to offer services and supports for patients who use illicit stimulants. Interventions can be guided by patients, recognising them as experts in the management of their stimulant use.